Studies on The Antimicrobial Activity of a New Bichalcone - Venkataraman, V.R.; Nagarajan, S.; A. Thomas, Philip (Asian Journal of Chemistry, 2010)
A new bichalcone viz. 2´,4´-dihydroxy-5´-(4-bromo) cinnamoyl-4-bromochalcone has been synthesised and Characterised by spectral studies. The antimicrobial activity of this bichalcone was tested against 7 isolates of fungi and 4 isolates of bacteria. The bichalcone has been found to exhibit significant activity on 3 isolates of fungi and 2 isolates of bacteria comparable to that of antifungal/antibacterial agents.